A Nanomechanical Investigation of Three Putative Anti-Erosion Agents: Remineralisation and Protection against Demineralisation - Ahmed Z. Abdullah; Anthony J. Ireland; Jonathan R. Sandy; Michele E. Barbour (Hindawi Limited, 2012)
An increasing interest in dental erosion as a clinical and scientific phenomenon has led to concerted efforts to identify agents which might protect against erosion. In this study, nanoindentation was used to investigate inhibition of erosive enamel demineralisation over time scales with direct clinical relevance. Nanohardness of polished human enamel specimens (n=8 per group) was measured at baseline (B), after demineralisation (D1: citric acid, 0.3% w/v, pH3.20, 20s), after treatment (T), and after a second demineralisation (D2: as above). Data were analysed using repeated measures ANOVA. All specimens exhibited a similar reduction in nanohardness B-D1 in the range 35.2-39.5%. The positive control solution (saturated hydroxyapatite solution) and 4500 mg/L fluoride as NaF significantly increased nanohardness D1-T by 19.9% and 24.1%, respectively, whereas 1400 mg/L fluoride as NaF, casein phosphopeptide-amorphous calcium phosphate mousse and negative control (deionised water) had no significant effect. Nanohardness at D2 was indistinguishable for all groups, with total reduction in nanohardness B-D2 of 31.6% (4500 mg/L fluoride), 35.2% (positive control), 39.9% (1400 mg/L fluoride), 42.4% (negative control), and 43.7% (CPP-ACP product). In summary, 4500 mg/L fluoride significantly increased the nanohardness of previously demineralised enamel and resulted in the smallest total reduction in nanohardness but there were few statistically significant differences among the groups.